Local banks, credit supply, and house prices - Kristian Blickle (Federal Reserve Bank of New York, 2018)
I study the effects of an increase in the supply of local mortgage credit on local house prices and employment by exploiting a natural experiment from Switzerland. In mid-2008, losses in U.S. security holdings triggered a migration of dissatisfied retail customers from a large, universal bank, UBS, to homogeneous local mortgage lenders. Mortgage lenders located close to UBS branches experienced larger inflows of deposits, regardless of their investment opportunities. Using variation in the geographic distance between UBS branches and local mortgage lenders as an instrument for deposit growth, I find that banks with an exogenous positive funding shock invest in strict accordance with their specialization (that is, local mortgage lending). Consequently, house price gains in neighborhoods around affected banks were more than 50 percent greater than those in neighborhoods around unaffected banks. I also find an increase in the number of employees at small firms, reliant on real estate collateral, in the former set of neighborhoods. My results show that local-mortgage-oriented banks affect house prices through the supply of credit and that bank specialization thereby plays an important role in the allocation of capital across sectors.
Keywords: G20; G21; R30; 330; credit supply; liquidity shock; house prices; local banking; employment